International Remittance Inflow and Poverty Reduction in Nigeria - Vivian A. ODISHIKA; Emmanuel I. AJUDUA; Princely E. IFINEDO (Communications of International Proceedings, 2022)
Developing countries, due to their poor GDP per capita and general poverty level, depend on remittances to better the lots of individuals with remittances, which is seen as an approach to poverty reduction. As a developing nation, Nigeria is the highest recipient of remittance in Sub-Saharan Africa, yet the country’s poverty rate is still alarming. This study examines the effect of international remittance inflow on economic growth in Nigeria by using time series data from 1990-2021. The a priori expectation is that there should be a positive relationship between remittance inflow and poverty reduction in Nigeria. A model using the poverty rate as the dependent variable and international remittance inflow, trade openness, index of financial development, and foreign exchange rate as the independent variables will be employed to test the study’s hypothesis. It is expected that findings from the study will benefit policymaking in Nigeria.
Keywords: Remittance; Poverty; Migration; Nigeria